2011
DOI: 10.3892/ijmm.2011.794
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP3A5 and ABCB1 gene polymorphisms and other factors on tacrolimus dosing in Caucasian liver and kidney transplant patients

Abstract: Abstract. Tacrolimus is a substrate of cytochrome P4503A (CYP3A) enzymes as well as of the drug transporter ABCB1. We have investigated the possible influence of CYP3A5 and ABCB1 single nucleotide polymorphisms (SNPs) and other factors (e.g. albumin, hematocrit and steroids) on tacrolimus blood levels achieved in a population of Caucasian liver (n=51) and kidney (n=50) transplant recipients. At 1, 3 and 6 months after transplantation, tacrolimus doses (mg/kg/day) and trough blood levels (C 0 ) were recorded an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
53
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 55 publications
9
53
0
4
Order By: Relevance
“…Carbon Monoxide-Bound Red Blood Cells Protect Hepatic P450 147 at ASPET Journals on May 11, 2018 dmd.aspetjournals.org is located in the liver, it is well known that intestinal P450 also plays an important role in the bioavailability of orally administrated drugs (Provenzani et al, 2011). Therefore, it will be necessary to investigate the changes in P450 levels in the gastrointestinal tract and evaluate the suppressive effects of CO-RBCs thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon Monoxide-Bound Red Blood Cells Protect Hepatic P450 147 at ASPET Journals on May 11, 2018 dmd.aspetjournals.org is located in the liver, it is well known that intestinal P450 also plays an important role in the bioavailability of orally administrated drugs (Provenzani et al, 2011). Therefore, it will be necessary to investigate the changes in P450 levels in the gastrointestinal tract and evaluate the suppressive effects of CO-RBCs thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…The trough blood levels (C 0 ) of tacrolimus were substantially lower in patients receiving livers with CYP3A5*1/*3 genotype (CYP3A5 non-expressers) than CYP3A5*3/*3 genotype (CYP3A5 expressers), which may hinder a stronger effect of the donor's genotype on tacrolimus dose requirements. [22] Based on the current study, genetic polymorphisms, especially SNPs, could have effects on simvastatin concentration and PK parameters. In the AUC inf group (Table 5), ARNT and five SLC transporters including SLC45A2 showed statistically strong differences (P < 0.001).…”
Section: Discussionmentioning
confidence: 84%
“…Shi et al (2013) studied tacrolimus pharmacokinetics and concluded that patient-specific differences in tacrolimus response could probably be explained by different intestinal CYP3A5 genotypes. A significant difference in tacrolimus daily dose and C/D ratios has also been reported between recipients with the CYP3A5 6986GG allele and those with the CYP3A5 6986AG/AA allele within 6 months of transplantation (Provenzani et al, 2011). A previous study also found that the genetic polymorphism of intestinal CYP3A5 in liver transplant patients was an important factor affecting tacrolimus blood concentration (Uesugi et al, 2006).…”
Section: Discussionmentioning
confidence: 89%